Synthesis of Some Functionalized Pyridazino[4,5-d]pyridazine Derivatives - (ARMAN) TAHERPOUR, AVAT; SHARIFNEZHAD, ZAHRA; AZAM SOUFALI, FROUGH; KHERADMAND, KHOJASTEH (Asian Journal of Chemistry, 2010)
The condensation reactions between ninhydrin and 1,3-dione compounds are one of the type extended reactions in various conditions. Compounds 1-3 were synthesized via the condensation of ninhydrin with barbituric acid, 1,3-dimethyl barbituric acid and 4-cyclopenten-1,3-dione in presence of sodium hydroxide and in Et-OH/H2O as solvent (in good yield). Compounds 4-6 as functionalized pyridazino[4,5-d]pyridazine derivatives could be made by simple reaction of 1-3 with hydrazine in very good yields. These compounds 1-3 and 4-6 show fluorescent properties.